Математика: учебное пособие для абитуриентов - Алешина О. Б. Ольга Борисовна; Долгушева Н. В. Надежда Васильевна; Киреенко С. Г. Светлана Григорьевна; Некряч Е. Н. Евгений Николаевич; Подскребко Э. Н. Эльвира Николаевна; Рожкова В. И. Валентина Ивановна; Рожкова С. В. Светлана Владимировна; Шахматов В. М. Валерий Михайлович (Томск, Изд-во ТПУ, 2012)
Заглавие с титульного экрана